Recontar passados: memória, história e literatura em K. - Santana, Gabriela Amorim de (2014)
After nearly forty years his sister disappearance, who was kidnapped, tortured and murdered by the Brazilian civil-military dictatorship, journalist Bernardo Kucinsky writes the novel `K.´ to tell the story of this family trauma, and thus, to bequeath this memory to all its readers. This monograph not only analyses the novel through a literary perspective, but also looks for history and memory theories outlines. Its first chapter examines the relations amongst memory, history and literature in the search to find the role played by each of them in the fight against oblivion and silence. The second one, delves into the remake of historical events distinguished by barbarity and focuses on the relations between literature and memory. Considering their relevance to the understanding of the novel, the third chapter, however, discusses such subject-matters as some concepts of Jewish culture, mostly those referring to memory, history, and death. In the end, this piece defends the need to hand down to future generations the traumatic memories, and most importantly, the subjectivity of feelings involved in these memories.